Integrating Islamic Environmental Ethics into Basic Education Curricula in The Gambia for a Sustainable Environment - Ceesay, Karamo; Sonko, Kebba Lang (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis paper explores integrating Islamic environmental ethics into the curriculum of basic education in the Gambia for a sustainable environment. In this paper, we adopted a qualitative approach to collect data through interviews with ten selected participants from 6 different regions in the Gambia. Our selection of participants was done purposively as we selected individuals who are well-versed in the subject matter. Our findings show that integrating Islamic environmental ethics into the basic education curriculum in The Gambia will not only have a long-term solution to the national environmental issues but rather will also breed a generation that will care for and love their environment, hence the country will have a sustainable ecosystem. However, this paper, therefore, recommends that the Ministry of Basic and Secondary Education to work with Islamic scholars in collaboration with the Ministry of Environment to develop a curriculum that will integrate Islamic environmental ethics in schools in The Gambia.AbstrakArtikel ini mengeksplorasi integrasi etika lingkungan Islam ke dalam kurikulum pendidikan dasar di Gambia untuk menciptakan lingkungan yang berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif dengan mengumpulkan data melalui wawancara terhadap sepuluh peserta yang dipilih dari enam wilayah berbeda di Gambia. Pemilihan peserta dilakukan secara purposif dengan memilih individu yang memiliki pengetahuan mendalam tentang topik ini. Temuan kami menunjukkan bahwa mengintegrasikan etika lingkungan Islam ke dalam kurikulum pendidikan dasar di Gambia tidak hanya akan memberikan solusi jangka panjang terhadap masalah lingkungan nasional, tetapi juga akan melahirkan generasi yang peduli dan mencintai lingkungan mereka. Sehingga, negara ini akan memiliki ekosistem yang berkelanjutan. Oleh karena itu, artikel ini merekomendasikan Kementerian Pendidikan Dasar dan Menengah untuk bekerja sama dengan para cendekiawan Islam serta berkolaborasi dengan Kementerian Lingkungan Hidup untuk mengembangkan kurikulum yang mengintegrasikan etika lingkungan Islam di sekolah-sekolah di Gambia. How to Cite: Ceesay, K., & Sonko, K. L. (2024). Integrating Islamic Environmental Ethics into Basic Education Curricula in The Gambia for a Sustainable Environment. TARBIYA: Journal of Education in Muslim Society, 11(2), 159-178. doi:10.15408/tjems.v11i2.42072.